Uterine Serous Papillary Carcinoma: A Retrospective Analysis of 22 Cases - Demir Özbasar; Serap Bozok; Taner Turan; İltac Küçükelçi; Gökhan Tulunay; Şadıman Altınbaş; Nurettin Boran; Ömer Faruk Demir; Mehmet Faruk Köse (Medical Network, 2008)
OBJECTIVE: The cases of 22 patients with uterine serous papillary carcinoma (USPC) were reviewed for this study. STUDY DESIGN: The data of 22 patients diagnosed with USPC was examined. 18 patients underwent formal staging surgery including type I hysterectomy, bilateral salphingo-oophorectomy, para-aortic and bilateral pelvic lymphadenectomy, appendectomy and omentectomy in our clinic. Four patients were sent to our clinic from other hospitals after primary surgery. Staging of the disease was based on the FIGO 1998. RESULTS: At the time of diagnosis the median age was 62.2 years. The most common clinic complaint was vaginal bleeding (86.3%). seven patients were stage I (31.8%), one was stage II (4.5%), eight were stage III (36.3%) and six were stage IV (27.3%). Median disease-free survival was 25 months. Recurrence was not influenced by the stage of disease, lymphatic metastasis, depth of myometrial invasion, adjuvant therapy and the type of adjuvant treatment. However, the recurrence was influenced by positive cytology and invasion of omentum. CONCLUSIONS: Staging surgery should be performed on patients with USPC. Invasion of omentum and positive cytology were poor prognostic factors. The effect of adjuvant therapy on prognosis is not clear.